2019
DOI: 10.1038/s41598-019-38493-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative nontumorous and tumorous human brain tissue assessment using microstructural co- and cross-polarized optical coherence tomography

Abstract: Optical coherence tomography (OCT) is a promising method for detecting cancer margins during tumor resection. This study focused on differentiating tumorous from nontumorous tissues in human brain tissues using cross-polarization OCT (CP OCT). The study was performed on fresh ex vivo human brain tissues from 30 patients with high- and low-grade gliomas. Different tissue types that neurosurgeons should clearly distinguish during surgery, such as the cortex, white matter, necrosis and tumorous tissue, were separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 43 publications
2
80
0
Order By: Relevance
“…However, the tendency of statistically higher values of the white matter in cochannel attenuation coefficient in comparison to tumor tissue is present in both studies (p < 0.001). Moreover, in our previous study, 27 it was shown that the presence of particular morphological patterns can lead to dramatic changes in coefficient values and that the cortex shows attenuation coefficients in the range of that of different tumor types. It should be noted that these calculations of the coefficients were made while disregarding the confocal factor of the OCT setup.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the tendency of statistically higher values of the white matter in cochannel attenuation coefficient in comparison to tumor tissue is present in both studies (p < 0.001). Moreover, in our previous study, 27 it was shown that the presence of particular morphological patterns can lead to dramatic changes in coefficient values and that the cortex shows attenuation coefficients in the range of that of different tumor types. It should be noted that these calculations of the coefficients were made while disregarding the confocal factor of the OCT setup.…”
Section: Discussionmentioning
confidence: 92%
“…Quantitative assessment of the OCT data can be based on the calculation of optical coefficients, for example, the attenuation coefficient [7][8][9][10]27 or machine-learning (classification) methods 28,29 and seems to be more objective. In patients, Böhringer et al 8 used an attenuation coefficient calculated from the log scale attenuation curves of areas with a homogeneous signal in the cross-section images, thus describing the linear part of the attenuation curve, but no data relating to sensitivity or specificity were demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Demonstrations on human and rat brain tissues have indicated the potential for differentiation of cancer and normal tissue. 94,137 We finally observe that, as well as optical properties, parametric OCT imaging can also be used to observe mechanical properties of tissue. 138,139 All such properties, optical and otherwise, show great potential to be combined with OCT attenuation imaging to provide a more comprehensive assessment of tissues.…”
Section: Complementary Optical Propertiesmentioning
confidence: 78%
“…Similar contrast was recently reported by Almasian et al 93 from an in vivo study, as summarized in Table 3. A recent study on ex vivo human brain tissue by Yashin et al 94 reported consistently lower attenuation coefficients of the tumorous tissue than the normal tissue. In addition, they observed a significant influence of tumor necrosis on the measured attenuation coefficients.…”
Section: Tablementioning
confidence: 94%
See 1 more Smart Citation